Chlorinated paraffins leaking from hand blenders can lead to significant human exposures. (December 2017) - Yuan, Bo; Strid, Anna; Darnerud, Per Ola; de Wit, Cynthia A.; Nyström, Jessica; Bergman, Åke
Abstract: Background: Chlorinated paraffins (CPs, polychlorinated n -alkanes) are versatile, high-production-volume chemicals. A previous study indicated that hand blenders leak CPs into prepared food. Objectives: (1) to estimate exposure to CPs from hand blender use compared to background CP exposure from diet; (2) to assess the risk from human dietary exposure to CPs from hand blender use; (3) to investigate how hand blenders leak out CPs. Methods: CPs were analyzed in food market baskets, in cooking oil/water samples (1 g oil/100 mL water) mixed using 16 different hand blenders, and in dismantled components of the hand blenders. Results: Dietary intake of CPs from food market baskets was calculated to be 4.6 μg/day per capita for Swedish adults. Total CP amounts in oil/water leakage samples ranged from < 0.09 to 120 μg using the hand blenders once. CP leakage showed no decreasing levels after 20 times of hand blender usage. CP profiles in the leakage samples matched those of self-lubricating bearings and/or polymer components disassembled from the hand blenders. Conclusions: Usage of 75% of the hand blenders tested will lead to increased human exposure to CPs. The intake of CPs for Swedish adults by using hand blenders once a day can raise their daily dietary intake by a factor of up to 26. The 95th percentile intake of CPs via using the hand blenders once a day exceeded the TDI for Swedish infants with a body weight < 7.2 kg. CP leakage came from blender components which contain CPs. The leakage may last several hundred times of hand blender use. Highlights: Human daily dietary exposure to chlorinated paraffins can be significantly increased by using hand blenders. Chlorinated paraffin intake via hand blender use exceeded the tolerable daily intake for infants with a body weight < 7.2 kg. C6 – C22 chlorinated paraffins were identified in the leakage from the hand blender use. The leakage came from blender components which contain chlorinated paraffins.